Gender Roles and Social Dynamics: An Anthropological Perspective on Thai Traditional Family Structures - มีไธสง, ธีระพงษ์ (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2024)
This study explores the significance of gender roles within traditional Thai family structures, examining their impact on social dynamics and individual identity formation. By analyzing the historical, cultural, and socioeconomic factors that shape family roles, this research provides insights into how traditional expectations influence behavior and relationships across generations. The findings reveal that Thai gender norms, deeply rooted in Buddhist principles and kinship ties, assign distinct roles to men and women, reinforcing a balance between public and private domains. However, modernization and globalization have introduced changes, leading to evolving perspectives on gender equality and shifting family dynamics. This anthropological study contributes to a broader understanding of how traditional family systems adapt in contemporary Thai society.